Emotional dependence as a risk factor in family violence, a public health problem - Beraún Vásquez, Hilda Rosario (2020)
Objective. To determine if emotional dependence is a risk factor for family violence of women treated in the Integrated Judicial Module on Family Violence of Huancayo. Methods. Quantitative, analytical, observational study of cases and controls. The sample consisted of 2 groups; the first of 83 women victims of family violence (case), the second of 21 women who did not report family violence (control). The questionnaire of emotional dependence was applied, for the test of hypothesis crossed tables were used, in order to analyze the odds ratio (OR). Results. It was determined that the average age was 32.5 years, the marital status was mostly cohabiting with 42,2%, the level of primary education, secondary, with 44.6%, the majority occupation, housewife in 63.9% and the type of violence they reported was physical and psychological in 41.3% of cases. The levels of dependence on the six factors of the scale reported high levels of emotional dependence; according to the results, it was OR 13.361, 95% CI 4.359-40.950. Conclusions.Sociodemographic characteristics are a risk factor for continuing in the cycle of violence, that, in a higher percentage, is associated with physical and psychological aggression. The high level of emotional dependence would explain the behaviors that the woman maintains in order to retain her partner; an attitude that invalidates her, humiliates her and keeps her immersed in a violent relationship. It is assumed that women with emotional dependence are 13 times more likely to be victims of family violence than those who did not present emotional dependence.